Discovery of a Beetroot Protease Inhibitor to Identify and Classify Plant-Derived Cystine Knot Peptides - Retzl, Bernhard; Hellinger, Roland; Muratspahić, Edin; Pinto, Meri E. F. [UNESP]; Bolzani, Vanderlan S. [UNESP]; Gruber, Christian W. (American Chemical Society (ACS), 2020)
Plant peptide protease inhibitors are important molecules in seed storage metabolism and to fight insect pests. Commonly they contain multiple disulfide bonds and are exceptionally stable molecules. In this study, a novel peptide protease inhibitor from beetroot (Beta vulgaris) termed bevuTI-I was isolated, and its primary structure was determined via mass spectrometry-based amino acid sequencing. By sequence homology analysis a few peptides with high similarity to bevuTI-I, also known as the Mirabilis jalapa trypsin inhibitor subfamily of knottin-type protease inhibitors, were discovered. Hence, we assessed bevuTI-I for inhibitory activity toward trypsin (IC50 = 471 nM) and human prolyl oligopeptidase (IC50 = 11 μM), which is an emerging drug target for neurodegenerative and inflammatory disorders. Interestingly, using a customized bioinformatics approach, bevuTI-I was found to be the missing link to annotate 243 novel sequences of M. jalapa trypsin inhibitor-like peptides. According to their phylogenetic distribution they appear to be common in several plant families. Therefore, the presented approach and our results may help to discover and classify other plant-derived cystine knot peptides, a class of plant molecules that play important functions in plant physiology and are currently being explored as lead molecules and scaffolds in drug development.